Experimental study of the heat transfer characteristics of single geothermal fracture at different reservoir temperature and in situ stress conditions. (5th May 2022) - Shu, Biao; Wang, Yimin; Zhu, Runjun; Liu, Leilei; Tan, Jingqiang; Dick, Jeffrey
Highlights: New fluid flow-through model and heat transfer coefficient equation are proposed. Temperature and stress affect energy extraction more than energy consumption. Energy extraction rate is much higher than pump energy consumption rate. Abstract: Deep geothermal energy in hot dry rock is a type of renewable energy which can serve as base load energy through enhanced geothermal systems. In previous studies, the effect of reservoir temperature and in situ stress on the heat transfer efficiency from rock to water was studied mainly for rock temperatures less than 100 °C. In this study, two experiments were conducted to explore the heat transfer coefficient and heat extraction efficiency of a single rock fracture with temperatures from 100 to 200 °C, and confining stresses from 4 to 20 MPa. A new heat transfer model for the fluid flow in a single fracture was established and heat transfer coefficient was derived. Experimental results shown that it is feasible to simplify the heat transfer coefficient equation by replacing the temperature of fracture surface with the temperature of rock sample because their difference is only 0.027% to 0.074%. The heat transfer coefficient increases by 21%, 48%, 94%, 117%, and 147%, while the energy extraction rate increases by 37%, 82%, 148%, 197%, and 299%, when rock temperature increases from 100 °C to 120 °C, 140 °C, 160 °C, 180 °C, and 200 °C, respectively. On the contrary, the heat transfer coefficient decreased by 16%, 22%, 27%, and 31%, while the energy extraction rate decreases by 19.3%, 29.0%, 35.7% and 40.4%, as confining pressure increases from 4 to 8, 12, 16, and 20 MPa, respectively. We also find that the temperature and confining pressure have less effect on the energy consumption of pump which is used to run the fluid flow in fracture, and the energy extraction rate is two to forty times of the pump energy consumption rate.